2003
DOI: 10.1097/00002030-200308150-00009
|View full text |Cite
|
Sign up to set email alerts
|

Mortality due to hepatitis C-related liver disease in HIV-infected patients in France (Mortavic 2001 study)

Abstract: In the post-HAART era, ESLD due to HCV is a growing cause of mortality in HIV-infected patients. Increased longevity attributable to HAART, and a higher prevalence of alcohol consumption, are probably involved in this trend.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
179
1
6

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(197 citation statements)
references
References 21 publications
11
179
1
6
Order By: Relevance
“…Consequently, cirrhosis caused by HCV has become a major cause of death in some areas. 9,10 These facts have led some experts to consider liver transplantation as a suitable therapeutic tool in coinfected patients with HCV-related ESLD. 11,12 The results recently reported in a case series dealing with the outcome of HIVinfected liver transplant recipients suggest that survival does not differ from that of HIV-negative patients.…”
Section: T Is Well Known That Human Immunodeficiency Virusmentioning
confidence: 99%
“…Consequently, cirrhosis caused by HCV has become a major cause of death in some areas. 9,10 These facts have led some experts to consider liver transplantation as a suitable therapeutic tool in coinfected patients with HCV-related ESLD. 11,12 The results recently reported in a case series dealing with the outcome of HIVinfected liver transplant recipients suggest that survival does not differ from that of HIV-negative patients.…”
Section: T Is Well Known That Human Immunodeficiency Virusmentioning
confidence: 99%
“…11 Once established, HIV-1 infection seems to increase the persistence of the hepatitis C virus, the level of HCV RNA and progression of HCV-related disease. [12][13][14][15][16] There are conflicting reports concerning whether HCV infection alters the course of HIV. 17 Some studies before the advent of highly active anti-retroviral therapy (HAART) suggested that survival and progression to AIDS were the same in patients with HCV/HIV co-infection as in those with HIV alone 18,19 whereas others suggested an adverse effect.…”
mentioning
confidence: 99%
“…Le carcinome hépatocellulaire ou cancer primitif du foie, est diagnostiqué à un âge plus jeune, et à un stade plus avancé chez les patients co-infectés VIH/VHB que dans la population mono-infectée, avec pour conséquence une survie plus courte [11]. En France, l'incidence annuelle du carcinome hépatocellulaire est 5 fois plus élevée dans la population co-infectée VIH/VHC que dans la population mono-infectée VHC [8]. …”
Section: Jean-charles Duclos-vallée Elina Teicher Daniel Vittecoq unclassified